2017
DOI: 10.1055/s-0043-100010
|View full text |Cite
|
Sign up to set email alerts
|

Zusammenhänge des Stationsklimas mit objektiven Rahmenbedingungen psychiatrischer Stationen

Abstract: The EssenCES, originally catered for forensic settings, proved to be useful to characterize general psychiatric wards. A number of suggestions regarding relevant setting conditions are clearly confirmed (like staffing level; open vs. closed wards). Remarkably, staff experience a higher level of on forensic than on general psychiatric wards. and are rated higher on general psychiatric wards. Heterogeneity of patients (vs. specialization of wards) is not positively related to climate characteristics; staff exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
3
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
3
4
3
7
Order By: Relevance
“…Additionally, the qualitative results indicate that facultative locked settings might be especially problematic regarding patients’ cohesion, as abrupt changes in the door status can have a negative impact on the relationships among patients. Our result that the door status does not apparently have an impact on patients’ cohesion from the perspective of the patients themselves corresponds to the study of Schalast and Sieß (29). Even though Blaesi et al (30) and Schalast and Sieß (29) indicated that there might be a positive influence of open doors on patients’ cohesion rated by mental health professionals, in line with Lo et al (31) and our qualitative results, this does not seem to be very consistent or clear.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, the qualitative results indicate that facultative locked settings might be especially problematic regarding patients’ cohesion, as abrupt changes in the door status can have a negative impact on the relationships among patients. Our result that the door status does not apparently have an impact on patients’ cohesion from the perspective of the patients themselves corresponds to the study of Schalast and Sieß (29). Even though Blaesi et al (30) and Schalast and Sieß (29) indicated that there might be a positive influence of open doors on patients’ cohesion rated by mental health professionals, in line with Lo et al (31) and our qualitative results, this does not seem to be very consistent or clear.…”
Section: Discussionsupporting
confidence: 90%
“…Some complex interventions, such as the so-called engagement model, aim to reduce coercion by improving the ward atmosphere, i.e., by creating an “atmosphere of hospitability and warmth” and, thereby, strengthening the therapeutic alliance (2628). There are also some studies which investigated ward atmosphere in relation to certain ward characteristics: Schalast and Sieß (29) examined the ward atmosphere experienced from patients and mental health professionals’ perspectives in different psychiatric settings, with slightly different results for both groups. Among others, they showed that some aspects of ward atmosphere were rated lower on locked than open wards.…”
Section: Introductionmentioning
confidence: 99%
“…B. im Rahmen anderer Untersuchungen durch "Öffnung" von Stationen bzw. durch den Vergleich offener und geschlossener Stationen bereits gezeigt werden konnte [3,4].…”
Section: Conclusion Relocation To New Buildings Alone Does Notunclassified
“…▶ Abb. 1 Einschätzungen des Stationsklimas durch Patienten (n t0 = 40; n t1 = 40) und Mitarbeiter (n t0 = 44; n t1 = 44) mittels EssenCES-D. Aus Patientenperspektive wurde das Stationsklima insgesamt etwas weniger günstig eingeschätzt als in einer vergleichbaren Studie aus der Akutpsychiatrie [30]. Im Vergleich zu Normwerten sind zu beiden Messzeitpunkten der Therapeutische Halt sowie der Zusammenhalt der Patienten durchschnittlich und das Sicherheitserleben eher unterdurchschnittlich ausgeprägt [24].…”
Section: Umsetzungunclassified